Pengaruh Penggunaan Media Gambar terhadap Hasil Belajar Siswa Kelas IV - Laras Erninda Saputro (Pedagogi: Jurnal Ilmu Pendidikan, 2019)
This study aims to obtain the real facts about the use of image media to improve learning outcomes of learners, knowing whether or not differences in learning outcomes of learners between the use of media images and the absence of the use of media images on a learning, which is a big influence on the results of participant learning students of class IV. In addition to these objectives, the purpose of the application of picture and picture method is to improve the spirit of learning of learners to follow the learning. The method used in this research is descriptive with short-acting Classroom Action Research (CAR). While the techniques and data collection tools used are observation techniques with data collection tools in the form of an association sheet distributed to teachers and learners as well as the final test as an evaluation for learners. From the results of published article search, it can be concluded the application of picture and picture method successfully applied and can improve student learning outcomes class IV. The purpose of every use of media in learning is very influential in every learning process because it will determine in which direction the learning will be successful or not in accordance with the objectives of learning to be achieved. In addition, the use of image media can not only be used for a single course but the use of these media can also be used for some other subjects, so the use of media images is very influential in the achievement of learning objectives.